(untitled) (Ameghiniana, 2015)
The Cerro Bandera Formation is a mostly pyroclastic continental unit exposed in isolated areas of east-central Neuquén Province, northwestern Patagonia. Several mammals from these deposits were previously reported and support a Colhuehuapian age (early Miocene) for these levels. New findings reveal that this unit bears a much more diverse assemblage and calls into question this age assessment. Here we describe three new species. Protypotherium sinclairi sp. nov. (Notoungulata, Interatheriidae) is similar in size to the Santacrucian Protypotherium australe Ameghino, but differs from all the species of the genus by having less reduced p3–p4 talonids. Doryperimys olsacheri gen. et sp. nov. (Rodentia, Neoepiblemidae) has hypselodont, prismatic cheek teeth that combine features of species of Perimys Ameghino and Scotamys antiquus Loomis. The systematic position of Leucokephalos maior sp. nov. within Caviomorpha is still uncertain, but it is definitively allied to the Deseadan Leucokephalos zeffiae Vucetich, Dozo, Arnal, and Pérez in sharing rooted cheek teeth with an almost identical early occlusal simplification that resembles the 8-shaped configuration of some early octodontoids and putative chinchilloids. The three species co-occur at a single fossil locality and stratigraphic level on the northeastern slope of Barda Negra; P. sinclairi and D. olsacheri are also recorded in other levels exposed in different isolated outcrops of the Cerro Bandera Formation. Doryperimys olsacheri –like other previously described rodents from this unit– is unknown in other presumably coeval mammal associations, but the biochronological and paleobiogeographic meaning of this assemblage is still under study. Resumen. DESCRIPCIÓN SISTEMÁTICA DE TRES NUEVOS MAMÍFEROS (NOTOUNGULATA Y RODENTIA) DEL MIOCENO TEMPRANO DE LA FORMACIÓN CERRO BANDERA, NORTE DE PATAGONIA, ARGENTINA. La Formación Cerro Bandera es una unidad continental mayormente piroclástica expuesta en áreas aisladas en el centro-Este de la Provincia de Neuquén, Noroeste de Patagonia. Varios mamíferos de estos depósitos fueron reportados previamente sustentando una Edad Colhuehuapense (Mioceno temprano) para estos niveles. Nuevos hallazgos revelan que esta unidad porta una asociación mucho más diversa y cuestionan esta edad. Aquí se describen tres nuevas especies. Protypotherium sinclairi sp. nov. (Notoungulata, Interatheriidae) es similar en tamaño a Protypotherium australe Ameghino (Santacrucense), pero difiere de todas las especies del género por tener los talónidos de p3–p4 menos reducidos. Doryperimys olsacheri gen. et sp. nov. (Rodentia, Neoepiblemidae) tiene molariformes hipselodontes, prismáticos, con caracteres combinados de las especies de Perimys Ameghino y de Scotamys antiquus Loomis. La posición sistemática de Leucokephalos maior sp. nov. dentro de los Caviomorpha aún es incierta, pero está definitivamente relacionado a Leucokephalos zeffiae Vucetich, Dozo, Arnal, and Pérez (Deseadense) por compartir molarifomes radiculados con una casi idéntica simplificación oclusal temprana que recuerda a la configuración en forma de ocho de algunos octodontoideos tempranos y supuestos chinchilloideos. Las tres especies ocurren positivamente en la misma localidad y nivel estratigráfico en el faldeo nororiental de la Barda Negra; P. sinclairi y D. olsacheri también se registran en otros niveles expuestos en diferentes afloramientos aislados de la Formación Cerro Bandera. Doryperimys olsacheri, así como otros roedores de esta unidad previamente descriptos, es desconocido en otras asociaciones de mamíferos presumiblemente coetáneas, pero el significado biocronológico y paleobiogeográfico de esta asociación aún está bajo estudio.